Pengembangan dan Integrasi Piranti Lunak Pendukung Sistem Akuisisi dan Reduksi Data Terowongan Angin Kecepatan Rendah Indonesia - Ivransa Zuhdi Pane (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2016)
Data acquisition and reduction system plays important roles in a wind tunnel test and determine the validity of aerodynamic characteristics information of the test object in Indonesian Low Speed Tunnel. Although it has been modernized recently, the main software components of the system are still requiring supporting counterparts to optimize the efficiency and the effectivity of the test execution. Several supporting softwares have been engineered so far and further developments are still in progress as attempts to fulfill those needs. Coordinating both main and supporting softwares in a well manner should be considered to realize fully integrated system which functions from the pre-test to the post-test phases as well as to anticipate various possible needs in the future. Index Terms—data acquisition and reduction system, software engineering, wind tunnel test